Risks in home-ownership: a perspective on the Netherlands - Teye, Alfred Larm; de Haan, Jan; Elsinga, Marja; Bondinuba, Francis (A+BE | Architecture and the Built Environment, 2018)
Purpose: Risk in home-ownership from mortgage providers’ perspectives within the euro zone has received more attention than individual home owner’s perspectives in the literature following the financial crisis in 2007/2008. The purpose of this paper is to explore the risk factors in home-ownership from the individual household’s perspectives within the owner-occupied housing sector of the Netherlands. Design/methodology/approach: The paper adopted a broader review of extant literature on the different concepts and views on risk in home-ownership. These concepts are unified into a framework that enhances our understanding of the perceived sophisticated risk within the owner-occupied sector in the Netherlands. Findings: From the perspective of the home owner, two main types of risks were identified: mortgage default and property price risk. The paper has unearthed a quantum number of factors which underline the above risks. The mortgage default risk factors include the initial amount of mortgage loan taken out, the future housing expenses and the income development of the owner-occupier. Family disintegration is also identified as one of the main causes of mortgage default in the Netherlands. Property price risk is influenced by income, interest rates and conditions in the social and private rental sectors. Research limitations/implications: Findings of the paper are based on review of the extant literature in the context of the Dutch housing market. Possible rigorous situational analysis using other tools are recommended for further research. Originality/value: This paper contributes to the much needed body of knowledge in the owner-occupied sector and provides a better understanding of risk in home ownership from the individual perspectives.